ENGLISH FOR TEP LEARNING MEDIA BASED VI-LEARN TO TRAIN VERBAL COMMUNICATION SKILLS OF CHEMISTRY STUDENT - Bertha Yonata; Maria Monica SBW; DIAN NOVITA (JCER (Journal of Chemistry Education Research), 2018)
Learning can not only be done in the classroom with direct face-to-face activities but can now be done with the help of IT, for example with learned learning. Although learning with vi-learn or e-learn cannot indeed replace overall face-to-face learning in the classroom. The world of education cannot be separated from technological advances such as this study because sometimes in carrying out classroom learning there are obstacles that cannot be avoided. These obstacles can be administrative in nature such as national holidays which coincide with the schedule of courses and cannot be replaced on another day due to limited space and insufficient time. In this study, learning tools for the English for TEP-based learning program have been developed to learn the verbal communication skills of students majoring in chemistry. From the data from the validation results, it can be concluded that learning devices consisting of enrichment modules and worksheets are feasible to be used in learning lessons. Likewise, from the response data, students showed a positive response from students in using enrichment modules and worksheets.